Rynek nieruchomości mieszkaniowych w Polsce - wykorzystanie metod taksonomicznych - Foryś, Iwona; Gdakowicz, Anna (Residential real estates market in Poland - application of taxonomic methods, 2006)
In the article the authors proposed the application of tajtonomic methods on the residential real estates market. A degree of development of voivodships with regard residential conditions can be determined by means of these methods. Voivodships of Poland and variables characterising this market were analysed. Number of accepted variables resulted from the need of synthetic formulation of the problem and on the other hand from available statistical data. They are the most frequently applied parameters describing residential market. It is possible to evaluate form of market of given residential voivodships. Suggested procedure can be taken advantage for taking a decision.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 335-342